2021
DOI: 10.1302/2058-5241.6.200146
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reaction to metal debris due to fretting corrosion between the acetabular components of modular dual-mobility constructs in total hip replacement: a systematic review and meta-analysis

Abstract: Modular dual-mobility (MDM) constructs can be used to reduce dislocation rates after total hip replacement (THR). However, there are concerns about adverse reaction to metal debris (ARMD) as a result of fretting corrosion between the metal liner and shell. This systematic review reports outcomes following THR using MDM components. It was registered with PROSPERO and conducted in line with Cochrane and PRISMA recommendations. Sixteen articles were included overall, with meta-analysis performed on relevant subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Ask patients for their evaluation and suggestions on the whole nursing intervention process. [15] reflect the severity of joint injury and the recovery of joint function according to symptoms and signs, tend to be self-assessed by patients, and pay more attention to patients' subjective experience, including pain, stiffness, and joint function of three dimensions, a total of 24 items, the total score of 96; the higher the score, the more serious the joint damage. Cronbach's α coefficient of each dimension was 0.878-0.956, and the intragroup correlation coefficient was 0.82-0.88.…”
Section: Nursing Methodsmentioning
confidence: 99%
“…Ask patients for their evaluation and suggestions on the whole nursing intervention process. [15] reflect the severity of joint injury and the recovery of joint function according to symptoms and signs, tend to be self-assessed by patients, and pay more attention to patients' subjective experience, including pain, stiffness, and joint function of three dimensions, a total of 24 items, the total score of 96; the higher the score, the more serious the joint damage. Cronbach's α coefficient of each dimension was 0.878-0.956, and the intragroup correlation coefficient was 0.82-0.88.…”
Section: Nursing Methodsmentioning
confidence: 99%
“…However, no patients required revision procedures for adverse local tissue reaction (ALTR), and ion levels decreased with follow-up, although data on long-term outcomes (> 2 years follow-up) was not reported. 23 Another systematic review by French et al 28 reported that the incidence of clinically significant elevated serum cobalt or chromium ion levels 1 µg/L or higher was 7.9%, and 7µg/L or higher was 1.8% over 279 cases in seven studies following MDM implantation. 24 As mentioned previously, there were two cases of rTHA reported in our study for complications related to metallosis, indicating that although ion levels in the short term may not be of concern, continued surveillance is needed in order to properly understand the risk of metallosis as a complication of MDM implants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing number of studies in the literature have raised concerns regarding the use of this type of implant. Dislocation rate after modDM THA is reported to range from 0.07% to 1.17% after primary procedures and even higher after revision surgeries [ 12 , 13 ]. During the last decade, intraprosthetic dislocation (IPD) has been reported as a specific failure mode of DM cups which can occur after both conventional DM THA [ 14 ] and modDM THA at early or late stage [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%